To rewrite the equation \( y = 3x - 24 \) in standard form, we want to rearrange it into the format \( Ax + By = C \), where \( A \), \( B \), and \( C \) are integers, and \( A \) is non-negative.
Starting with:
\[ y = 3x - 24 \]
we can rearrange it by moving all terms involving \( x \) and \( y \) to one side of the equation:
\[ -3x + y = -24 \]
For standard form, we typically want \( A \) to be positive, so we can multiply the entire equation by -1:
\[ 3x - y = 24 \]
Now, the equation is in standard form:
\[ 3x - y = 24 \]
Thus, the standard form of the equation is \( 3x - y = 24 \).